Identify drying kinetic parameter of Ficus Deltoidea and Centela Asiatic a using modified page model and two term model / Nurul Syuhada Roslan. - Roslan, Nurul Syuhada (2009)
In this study, identify drying kinetic parameter of Ficus deltoidea and Centella asiatica have been investigated using a convective drying. Ficus deltoidea and Centella asiatica were determining at different temperatures for 40°C, 50°C and 60°C with constant air velocity at 1.5 m/s. Sample weight was measured by using tray dryer. Drying kinetic exhibit only has one falling rate period. Air temperature affected the drying curves decreasing the drying time of samples. The usefulness of two different mathematical models to stimulate and during kinetic of Ficus deltoidea and Centella asiatica are Two Term model and Modified Page model solve by the separation of variable methods. The models were compared by the Minimum Sum Square Error (MSSE). A had the lowest value of MSSE for Ficus deltoidea is Modified Page model at temperature 50°C and for Centella asiatica has the lowest value of Two term model at temperature 60°C.